2006
DOI: 10.1073/pnas.0511019103
|View full text |Cite
|
Sign up to set email alerts
|

Unique, common, and interacting cortical correlates of thirst and pain

Abstract: This study used positron-emission tomography to establish the patterns of brain activity involved in the isolated and concurrent experiences of thirst and pain. Ten subjects were scanned while experiencing pain evoked with noxious pressure, while experiencing thirst after the infusion of hypertonic saline, and while experiencing pain when thirsty. After the onset of thirst, noxious pressure evoked more intense sensations of pain. Noxious pressure did not change subjective ratings of thirst. Thirst caused activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 40 publications
(53 reference statements)
6
41
0
Order By: Relevance
“…From the very first neuroimaging study of thirst (16), this region has consistently shown activation in response to thirst using different imaging techniques (i.e., PET, arterial spin labeling) and varied experimental manipulations of physiology (17)(18)(19). In addition to being involved in the neural representation of thirst, the pACC is also part of the cortical network involved in swallowing (20,21), and in monkey it has been demonstrated that the cingulate cortex has cortical projections to pons (22), an area that contains nuclei implicated in the initiation of swallowing (23,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the very first neuroimaging study of thirst (16), this region has consistently shown activation in response to thirst using different imaging techniques (i.e., PET, arterial spin labeling) and varied experimental manipulations of physiology (17)(18)(19). In addition to being involved in the neural representation of thirst, the pACC is also part of the cortical network involved in swallowing (20,21), and in monkey it has been demonstrated that the cingulate cortex has cortical projections to pons (22), an area that contains nuclei implicated in the initiation of swallowing (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…S2). Ratings of thirst were made using a 0-10 rating scale according to a previously reported procedure (18). The level of cycling exercise was standardized by calculating the heart rate reserve (HRR) for each participant: HRR = (220 -age in years) -resting heart rate (RHR), and then ensuring that participants maintained their heart rate at the sum of the RHR plus 60% of the HRR for the duration of the exercise period, using feedback on their heart rate provided by a telemetric device.…”
Section: Methodsmentioning
confidence: 99%
“…Previous reports from this group have identified activations associated with thirst (13,14,26) and plasma Na (27) in two regions of the cingulate cortex: the pACC and the aMCC (summarized graphically in ref. 28).…”
Section: Discussionmentioning
confidence: 99%
“…The contrast between maximum thirst and baseline revealed two loci of activation in the cingulate cortex in both groups: the aMCC [Y, (12,24,26); O, (12, 18, 48); Talairach coordinates] and the pACC (BA32) [Y, (8,38,2); O, (14,36,14)] (Fig. 2).…”
Section: Figmentioning
confidence: 99%
“…S1A). Ratings of thirst were made by using a 0-10 rating scale (with 0 indicating thirst and 10 indicating maximum thirst) according to a previously reported procedure (74). The degree of exercise was standardized by (i) calculating the heart rate reserve (HRR) for each participant before exercise [HRR = (220 − age in years) − resting heart rate (RHR)]; (ii) adding 60% of the HRR to the RHR; and (iii) ensuring that each participant maintained their heart rate at this value (RHR + 0.6*HRR) for the duration of the exercise period by using feedback on their heart rate provided by a telemetric device.…”
Section: Methodsmentioning
confidence: 99%